INCORPORATING GENRE ANALYSIS IN TEACHING WRITING - Nurhasanah Halim (Getsempena English Education Journal, 2019)
Regarding the improvement in previous studies of implementing genre approach in English classes, this study was aimed at incorporating genre analysis in teaching writing. Genre analysis is a systematic analysis used to present patterns of language to students so that they can get sufficient understanding of the given genre. A particular genre is specified by moves describing how a text stretches to achieve its communicative purposes. By understanding the moves, students are expected to produce English written text. Through a classroom research, this study reported (1) how to incorporate the genre analysis to teaching writing of the job application letter, and (2) what students’ response to incorporating the genre analysis in the teaching of writing job application letter in English. Data were collected through students interviews, classroom observation, and reflective journals.